2015
DOI: 10.1097/mrr.0000000000000108
|View full text |Cite
|
Sign up to set email alerts
|

Six-month functional recovery of stroke patients

Abstract: The aim of this study is to compare the time-course changes in neurologic impairments (trunk control, motor function, sensory, and cognition) and recovery in functional impairments (activity of daily livings and gait) simultaneously from initiating rehabilitation to 6 months after stroke. Consecutive stroke patients were recruited from the department of nervous surgery, and transferred into the department of rehabilitation medicine and continued on treatment during the acute stage. Outcome measures were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
193
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(207 citation statements)
references
References 27 publications
7
193
1
6
Order By: Relevance
“…Between 3 and 6 months after stroke, most previous studies report little or no observable recovery [5,7]. In contrast, Lee et al [6] showed a small but significant improvement in all recovery variables 3-6 months after a stroke, with the exception of lower-body motor function, indicating that recovery had not yet plateaued. In addition, it is known that most of the recovery of gait and motor function generally occurs within 6 months after a stroke [8,9].…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Between 3 and 6 months after stroke, most previous studies report little or no observable recovery [5,7]. In contrast, Lee et al [6] showed a small but significant improvement in all recovery variables 3-6 months after a stroke, with the exception of lower-body motor function, indicating that recovery had not yet plateaued. In addition, it is known that most of the recovery of gait and motor function generally occurs within 6 months after a stroke [8,9].…”
Section: Introductionmentioning
confidence: 59%
“…Improvement in motor function in the lower body is observed in -65% of patients with initial motor deficits [3]; however, the probability of recovery of normal functioning in the upper limbs is much lower (< 15%) [4]. Additionally, the rate of clinical recovery is relatively rapid during the first few weeks after a stroke, and then decelerates 1-3 months later [5,6]. Between 3 and 6 months after stroke, most previous studies report little or no observable recovery [5,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The different follow-up time points (3 months for the interventional group vs 6 months for the medical therapy group) should not have a significant influence on the study results considering that (1) the primary analysis was discharge outcome and (2) the theoretical advantage of more recovery time should have favored the medical therapy group 15. It should be noted that the groups derived from different cohorts and study periods; the advancements in medical management over time might have played an important role in the study results.…”
Section: Discussionmentioning
confidence: 99%
“…[16383940] Tatemichi et al . demonstrated a substantial body of high-quality research evidence for the effectiveness and cost-effectiveness of rehabilitation in patients with ABI.…”
Section: Discussionmentioning
confidence: 99%